Analisis Kebutuhan Pengembangan Instrumen Tes Penilaian Literasi Sains Berorientasi TIMSS Siswa SD Kelas V - Barus, Robi Agape; Rusilowati, Ani; Ridlo, Saiful (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
Scientific literacy is a crucial competency needed to face the challenges of the 21st century. This is because scientific skills can equip learners to tackle various challenges in the global era. Scientific literacy, which involves understanding information, scientific knowledge, and facts in daily life, is essential for students to better prepare them for the era of scientific advancement and technology utilization in the present and future. The research objective is to identify the needs and issues teachers and students face related to science literacy test instruments in the 5th grade. This study applies qualitative research methods with descriptive data analysis obtained from interviews and observations with 5th-grade teachers and distributing a needs questionnaire to students. The research found that teachers still need to get science literacy test instruments; they acknowledge the importance of these instruments to measure and enhance students' scientific literacy but are hindered by a lack of ability to develop such instruments. Teachers' test instruments are still basic and mainly focus on measuring aspects of science content. Most students also recognize the importance of scientific literacy. In conclusion, both teachers and students require science literacy test instruments to measure and enhance students' scientific literacy.